Design and analysis of cloth dryer cabinet by utilizing heat rejected from air conditioning system - Muhammad Farid, Kamberi (2009)
Nowadays cabinet dryer is widely use, especially for those who are busy working. Besides that, most of the laundries today have a dryer. It is not just because it can run their operation all the time, but they also can prevent the risk to the cloths that might lost or get dirt. Cabinet dryer in the market nowadays is using electrical power as a source in generating heat. The other alternative in manipulation of heat being study to create a new cabinet dryer that make a benefit of waste. From the study, it found that split air conditioning system had waste heat that rejected from it condensing unit. The rejected heat had bad effect to the environment. This project is the study in manipulation of the heat rejected from air conditioning system to dry cloths inside a cabinet dryer. It cover the design of cabinet, investigation of the effectiveness and comparison to the several kind of other dryer. The comparison been made between natural drying and drying by commercial cabinet dryer According to the comparison, it shows that drying by heat rejected from condensing unit is better compares to the natural drying. But commercial dryer have a better drying rate compares to the cabinet dryer that manipulate the heat from condensing unit.From this project, it prove that the cabinet dryer utilizing heat rejected by air conditioning system is effective and worth even the performance is not good as commercial cabinet dryer, it is free and environmental friendly.